2012
DOI: 10.1371/journal.pmed.1001184
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Rupture by Intended Mode of Delivery in the UK: A National Case-Control Study

Abstract: A case-control study using UK data estimates the risk of uterine rupture in subsequent deliveries amongst women who have had a previous caesarean section.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
180
8
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 172 publications
(209 citation statements)
references
References 28 publications
15
180
8
6
Order By: Relevance
“…Cases included in the analysis of socioeconomic inequalities were women who suffered from one of the following six conditions of severe maternal morbidity directly attributable to pregnancy causes: AFE, 32 AFLP, 30 eclampsia, 28 peripartum hysterectomy, 31 peripartum haemorrhage 129 and uterine rupture. 181 For the ethnic inequality study, in addition to these six conditions, cases were included from a further five conditions: antenatal pulmonary embolism, 29 stroke in pregnancy, 74 placenta accreta, 72 HELLP syndrome 54 and severe sepsis. 99 These data sets represented the entirety of data available on direct maternal morbidities and control women at the time the analyses were conducted.…”
Section: Secondary Data Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Cases included in the analysis of socioeconomic inequalities were women who suffered from one of the following six conditions of severe maternal morbidity directly attributable to pregnancy causes: AFE, 32 AFLP, 30 eclampsia, 28 peripartum hysterectomy, 31 peripartum haemorrhage 129 and uterine rupture. 181 For the ethnic inequality study, in addition to these six conditions, cases were included from a further five conditions: antenatal pulmonary embolism, 29 stroke in pregnancy, 74 placenta accreta, 72 HELLP syndrome 54 and severe sepsis. 99 These data sets represented the entirety of data available on direct maternal morbidities and control women at the time the analyses were conducted.…”
Section: Secondary Data Analysismentioning
confidence: 99%
“…This represents only a summary of key points; many more specific messages for care are reported in the publications about individual conditions and these should be referred to for further detail. 54,71,72,181,220,221 The incidence of the specific morbidities most commonly leading to maternal death in the UK We examined the incidence of AFE, severe maternal sepsis, uterine rupture, HELLP syndrome and placenta accreta/increta/percreta. Because the studies conducted were national cohort or case-control studies, we were able to estimate incidence of each condition with a relatively high degree of precision.…”
Section: Key Findings and Implications For Practice Or Policymentioning
confidence: 99%
See 1 more Smart Citation
“…But this remaining incidence 1.14% is still very high in comparison to other countries as 0.02% in UK (Fitzpatrick et al), 0.0521% in China (Xiaoxia B et al), 0.67% in Pakistan (Nousheen et al), 0.85% in northern Nigeria (Akaba GO et al), 0.225% in Tanzania (Kidanto HL et al), 1.46% in southern Nigeria (Kelechi et al) and even other parts of India also as 0.07% in Mumbai (Nagarkatti RS et al). [7][8][9][10][11][12] We have observed that rupture uterus occurred much more frequently in unscarred uterus in our study group even after implementation of JSY. This might be due to deliveries conducted by untrained personnel in rural sectors where either proper medical care is still not available or the ill-informed, uneducated patient and family are still reluctant to seek any trained help.…”
Section: Anand Rs Et Al Int J Reprod Contracept Obstet Gynecol 2016mentioning
confidence: 88%
“…But the remaining maternal mortality (4.88%) is still higher in comparison to the studies like Xiaoxia B et al (0%), Fitzpatrick et al (1.3%) and lower to studies Akaba et al (14.7%), Nousheen et al (8.19%), Hussain L et al (6.6%). [7][8][9][10] We have observed that perinatal mortality was almost same in both groups i.e 93.93% and 95.12% in group 1 and group 2 respectively. This incidence of fetal case fatality rate is comparable to Akaba et al (90.7%), Kidanto H. L. et al (96.3%) and Nousheen et al (83.6%).…”
Section: Anand Rs Et Al Int J Reprod Contracept Obstet Gynecol 2016mentioning
confidence: 99%